Revisiting Second Wave Feminism in the Light of Recent Controversies - Power, Nina (Identities: Journal for Politics, Gender and Culture, 2020)
This paper revisits elements of second wave feminism—in its psychoanalytic, radical, materialist, Marxist and deconstructionist aspects—the better to understand how it is we might define sexual difference today. The vexed question of sexuation, of what it means to be a woman in particular has today generated great tensions at the theoretical, legal and philosophical level. This paper is an attempt to return to aspects of the second wave—an unfinished project where many enduring feminist concerns were for the first time thoroughly and metaphysically articulated—the better to defend the importance of sexual difference. To this end, the transcendental and parallax dimensions of sexed life will be discussed, alongside a defence of the centrality of the mother to our thinking about the relevance and necessity of preserving the importance of sexual difference, not only for thought but also for political and legal life. Author(s): Nina Power Title (English): Revisiting Second Wave Feminism in the Light of Recent Controversies Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 28-35 Page Count: 8 Citation (English): Nina Power, “Revisiting Second Wave Feminism in the Light of Recent Controversies,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020): 28-35. Author Biography Nina Power, Independent Researcher Nina Power is a philosopher and writer, and the author of many articles on politics, feminism and culture. She is the author of One-Dimensional Woman (2009) and the forthcoming What Do Men Want? (2021). She is currently teaching at Mary Ward and has previously taught at the University of Roehampton and many other institutions